The Effect of Debt Level, Liquidity and Company Size Against Profitability - Eny Purwaningsih (Journal of Multidisciplinary Science, 2024)
The purpose of this research is to analyse the effect of debt level, liquidity, and company size on profitability. There are independent variables including debt level using Debt to Asset Ratio, liquidity using Loan to Deposit Ratio, company size using the natural logarithm of total assets and the dependent variable is profitability using Return on Equity. The sample in this research is the financial sector service entities in the bank sub-sector listed on the Indonesia Stock Exchange for the period 2018-2021 using purposive sampling method. In this research there are 26 entities that support the research sample criteria, so that 104 financial statement data are obtained. This research method uses classical assumption tests such as normality, multicollinearity, heteroscedasticity and autocorrelation used in this research. Furthermore, the hypothesis is tested with F test, t test and coefficient of determination. The research test uses multiple regression analysis with multiple regression equation models. Based on the test findings, it is known that simultaneously shows that the level of debt, liquidity, and company size have a simultaneous impact on profitability in financial sector service entities in the bank sub-sector listed on the Indonesia Stock Exchange in 2018-2021. Partial test findings show that the level of debt has no impact on profitability, liquidity and company size have a positive impact on profitability.